THE ASSOCIATION OF CATARACT TYPE ON CENTRAL CORNEAL THICKNESS AFTER PHACOEMULSIFICATION CATARACT SURGERY: Cataract Type on Central Corneal Thickness - Abbas, Hussnain; Rauf, Abdul; Perveen, Shagufta; Mehmood, Shahid Hamid; Hussain, Irshad; Naimat, Khalid (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess any association between the type of cataract and the central corneal thickness at pre-operative and postoperative three-day and one-month appointments after phacoemulsification surgery.Study Design: Prospective, comparative study.Place and Duration of Study: Eye Department Combined Military Hospital Multan, from Jun 2020 to Apr 2021.Methodology: A total of 89 patients requiring cataract surgery by phacoemulsification were recruited. Age and gender were recorded for each patient. Patient’s type of cataract based on maturity was recorded before the surgery. Phacoemulsification cataract surgery using ‘divide and conquer’ technique was carried out. Patients’ central corneal thickness was measured at the pre-operative, three-day post-operative and one-month post-operative appointment using traditional non-contact tonopachymeter.Results: There were 49 (55.1%) male and 40 (44.9%) female patients with a mean age of 62.15 ± 12.40 years. No significant association was found between the type of cataract and central corneal thickness at the three-time intervals (p=0.14). Central corneal thickness significantly increased from 0.48 ± 0.04 mm pre-operatively to 0.51 ± 0.04 mm at the three-day post-operative appointment (p